Anaphylaxis in a Newborn Due to Ampicillin - Nagehan Katipoğlu; Abdullah Barış Akcan; Münevver Kaynak Türkmen (Galenos Yayinevi, 2018)
Anaphylaxis, an allergic reaction that is rapid in onset, is rare in the neonatal period due to immaturity of the immunological system. A case of threeday- old male neonate with ampicillin-induced anaphylaxis is reported here. Although drug allergies are rare in newborns, due to their life-threaten features, close monitoring is important.